2016
DOI: 10.1007/s10517-016-3505-0
|View full text |Cite
|
Sign up to set email alerts
|

Intensity of Oxidative Stress in Mongoloid and Caucasian Patients with Type 1 Diabetes Mellitus

Abstract: Specific features of LPO were studied in Mongoloid and Caucasian patients with type 1 diabetes mellitus. The intensity of LPO in Mongoloid patients was lower than in Caucasians: the level of primary and intermediate products was by lower 1.53 and 1.83 times, while total antioxidant activity was elevated by 1.44 times, which was also supported by oxidative stress coefficient (1.35 in Mongoloids and 2.32 in Caucasians). These differences suggest that differentiated approach is required for the treatment of these… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 8 publications
0
5
0
3
Order By: Relevance
“…Thus, the data of the Research Center for Family Health and Human Reproduction Problems showed that Buryats are characterized by a low frequency of DM1 and not similar to Caucasians HLA-alleles and genotypes association [58]. Low genetic conditionality of DM1 in the Buryat group contributes to the development of certain features of metabolic reactions in representatives of this ethnic group, which allowed them to be attributed to the group of "relative ethnic norm" [60]. Thus, it was shown that the intensity of LPO processes in patients of Buryat ethnic group with DM1 was reduced compared to Russians (lower level of primary and intermediate products, increased values of total antioxidant activity), which is confirmed by low values of OS coefficient.…”
Section: Deactivation Of the Insulin Signaling Pathwaymentioning
confidence: 99%
“…Thus, the data of the Research Center for Family Health and Human Reproduction Problems showed that Buryats are characterized by a low frequency of DM1 and not similar to Caucasians HLA-alleles and genotypes association [58]. Low genetic conditionality of DM1 in the Buryat group contributes to the development of certain features of metabolic reactions in representatives of this ethnic group, which allowed them to be attributed to the group of "relative ethnic norm" [60]. Thus, it was shown that the intensity of LPO processes in patients of Buryat ethnic group with DM1 was reduced compared to Russians (lower level of primary and intermediate products, increased values of total antioxidant activity), which is confirmed by low values of OS coefficient.…”
Section: Deactivation Of the Insulin Signaling Pathwaymentioning
confidence: 99%
“…Так, было доказано, что степень интенсивности липопероксидных процессов у пациентов бу-рятского ýтноса с сахарным диабетом 1-го типа снижена по сравнению с русскими (более низкий уровень первичных и промежуточных продуктов, повышенные значения общей антиокислительной активности), что подтверждается и низкими зна-чениями коýффициента окислительного стресса [77]. Течение СД1 у бурят также характеризует-ся сниженными значениями общих липидов, три-ацилглицеридов, общего холестерина и липопро-теинов низкой плотности, что, вероятно, может способствовать более благоприятному течению заболевания у бурят [78].…”
Section: обзоры и лекцииunclassified
“…In conditions of increased generation of LPO products are observed changes permeability of cell membranes for a lot of ions, nonelectrolytes, and macromolecules [27]. This processes in loss of barrier function of cell membranes that is the pathogenesis of different diseases, including development of vascular disorders in T1DM due to lipid peroxidation activation during prolonged hyperglycemia [9,28]. The observed increase in LPO activity cannot provide sufficient information about the redox-status in patients with T1DM, because it indicates one aspect of the study, LPO excluding of AOD activity.…”
Section: Resultsmentioning
confidence: 99%
“…Some studies revealed that low morbidity of T1DM among the aboriginal people in Arctic and Siberian regions resulted from the presence of the protective allele's genes for this disorder [6]. The prevalence of this form of diabetes among indigenous people in the Buryatia Republic is 24.18 per 100,000, which is below the average level in Russia (224.5 per 100,000) [8,9].…”
Section: Introductionmentioning
confidence: 99%